UMP Foundation Excellence Incentive (Platinum) for excellent students - Nur Sa’adatul Afzan, Jusoh (2020)
Nurnajjah Ashuha Adipso, the final year student from the Faculty of Industrial Sciences and Technology (FSTI), Universiti Malaysia Pahang (UMP), did not expect to be among the 30 students to receive the UMP Foundation Excellence Incentive (Platinum) worth RM500 for her excellent result this semester.